Implementasi Penerapan Media Audio Visual dalam Meningkatkan Keterampilan Menulis Cerpen Siswa Kelas IV SDN 02 Rengging - Oktavia Syntya; Yushinta Eka Farida; Dwiana Asih Wiranti (Qalam : Jurnal Ilmu Kependidikan, 2023)
This research aims to evaluate the effectiveness of the implementation of audio visual media in improving short story writing skills in class IV students at SDN 02 Rengging. The research method used is a descriptive qualitative method. Qualitative research is research whose specifications are systematic, planned and structured from the beginning to the creation of the research design to the implementation stage. Research participants were fourth grade students at SDN 02 Rengging. The application of audio-visual media is carried out through the use of story visualization, sound recordings and interactive multimedia as tools in short story writing activities. The results of the research show that the implementation of audio visual media has a positive impact on improving students' short story writing skills. Visualization of stories and sounds provides inspiration and makes it easier to understand the concept of short story writing. Apart from that, the use of interactive media also increases students' creativity in designing and developing short story ideas. Students' attraction and interest in learning to write short stories was also observed to be higher with this approach. This research also highlights the importance of the teacher's role as a guide, although audio-visual media can make a significant contribution. Therefore, the results of this research support the idea that the implementation of audio-visual media can be an effective strategy in improving the short story writing skills of class IV students at SDN 02 Rengging, creating a dynamic and creative learning environment.